The Problems Existing in the Development of Rural E-commerce in Henan Province - Yan, Yang (International Journal of Global Economics and Management, 2024)
This paper aims to explore the problems existing in the development of rural e-commerce in Henan Province and propose corresponding solutions. Through the integration of existing research results, combined with field surveys and case analyses, it deeply analyzes the challenges and difficulties in the development of rural e-commerce in Henan Province, thereby providing theoretical support and practical guidance for further development in this field.